Aspectos Psicológicos implicados no processo de Proteção a Vítimas e Testemunhas de Violência- PROVITA - Valadão, Geny Rodrigues (2005)
The present work has as objective to contribute for a reflection process on the psychological aspects implied in the process of protection of the Programa de Apoio ás Testemunhas, Vítimas e Familiares de Vítimas de Violência - PROVITA, emphasizing the change of identity, compatible and incompatible personality, the role of the psychologist and the freedom in the clandestinity. It was based on articles published by GAJOP and material obtained with the representative of Secretaria de Promoção e Defensa dos Direitos Humanos, in Brasilia. The objective of the study was focalized in psychological aspects of victims and witness and about challenge that they face to develop a new personal structure based on values of their new environment. From the referencial of the critical theory, it became evident the contradictions existent in the process of protection of PROVITA to reduce physical and psychological discomfort of the victims and witness, the suffering and the traumatic breaking lived by the individual. The research brings a set of information on the public politics of security that a few years ago nobody thought about it in Brazil. It evidences some problems that PROVITA will still face to become a space of contradiction and desorganization of the artifice of the social, economic politician system that command and propitiate total poverty and absence of social and political projects that guarantee the executation of the Human Rights.